Tekst artystyczny między stylami i gatunkami (genologiczne „silva rerum" nowej i najnowszej literatury polskiej - Dąbrowska, Elżbieta (Przestrzenie Teorii, 2007)
The paper discusses the state of literary art whose genres result from an interplay of various genological instruments. Multidimensional relations between styles, forms, and languages (uncommon and common speech practices) together with intertextual mechanisms of "making texts from texts" result in hybrid forms of expression, in their multidimensional and "blurred" genre classifications.